Murray, Tony. London Irish Fictions: Narrative, Diaspora and Identity - Standlee, Whitney (ABEI Journal, 2012)
Murray, Tony. London Irish Fictions: Narrative, Diaspora and Identity. Liverpool: Liverpool University Press, 2012.